2002
DOI: 10.1053/rmed.2002.1301
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output increases prior to development of pulmonary edema after re-expansion of spontaneous pneumothorax

Abstract: Pulmonary edema following reexpansion of spontaneous pneumothorax is an uncommon complication. The underlying mechanism of this condition is unclear. We report the hemodynamic characteristics in a series of 7 male patients with spontaneous large (>50%) pneumothoraces of > or = 24 h and correlate the changes with reexpansion pulmonary edema (REPE). A pulmonary artery floatation catheter was inserted and hemodynamic data were obtained before therapeutic chest tube insertion, 1 h after chest tube insertion and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…Several studies have demonstrated that the incidence of REPE is higher when the size of the pneumothorax is larger [10,23,24]. These finding are consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that the incidence of REPE is higher when the size of the pneumothorax is larger [10,23,24]. These finding are consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The detection rate of REPE was higher in our study than other earlier studies, possibly due to the application of negative pressure after thoracostomy and the use of CT imaging to detect REPE 15. CT imaging of the chest was used in this study, because of its higher accuracy and sensitivity in diagnosing REPE.…”
Section: Discussioncontrasting
confidence: 57%
“…The etiology of re‐expansion pulmonary oedema (REPE) remains speculative, although hemodynamic changes occur and sympathetic overdrive may also participate. The main mechanism of REPE is the increased pulmonary vascular permeability; however, changes in cardiac output have also been described in patients who developed REPE [10].…”
Section: Discussionmentioning
confidence: 99%